(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
We are social beings and, so in some way or other we needhelp and guidance of others. Mother, father, grandparents, and teachers and otherelders as well as home, school and society guide youngsters for successfulliving. The student’s life is getting complex day by day. Students in the twenty-first century have facing many complex and difficult situationsi.e. to make wise curricular and othercurricular choices, to acquire basic study skills for optimum achievement, adjustment with peersetc. Due to explosion of knowledge, industrialization and changes in socio-economic setup the need of professional guidance is felt in the present day society. In the present time the aim of education is to achieve the fullest possible realization of possibilities inherent inthe individual. The education fostersall aspects of an individual‘s personality.